Loneliness in Middle-Aged and Older Adults: Effects of Social Environments - Inna Murtazina; Kristina Krupina; Olga Strizhitskaya (Behavioral Sciences)
Loneliness is a common subjective condition that is associated with distress and negative outcomes for psychosocial functioning and well-being, and it is grounded in destructive or inadequate social functioning. Social interactions are considered one of the key factors determining loneliness, and similarly to social interactions, loneliness can occur in different domains. While a solid body of research is focused on loneliness as a general condition, there are few studies that investigate loneliness from a multidimensional perspective, particularly combining general and domain-specific loneliness. In the present study, we conceptualized loneliness as a complex phenomenon. We focused on the associations between different types of loneliness and the characteristics of social environments. The participants were 140 adults aged 45–73 (58.9% females). The methods involved the Multidimensional Inventory of Loneliness Experience, the Social and Emotional Loneliness Scale (SELSA-S), the “Sociotropy—Self-Sufficiency” Questionnaire, and the assessment of demographic characteristics (age and sex). To test our hypothesis, we applied regression path modeling. The results showed that general loneliness predicted both family and non-family loneliness. We also found that general loneliness increased experiences of social uncertainty, while non-family loneliness decreased positive relations with others. No age effects were found. An effect of sex was found for social uncertainty and positive relations with others.